“Evaluación de propiedades físicas de 4 híbridos de tabaco negro de capa para puro en Juan Guerra-San Martín” - Blancas Ríos, Maria Elena (2002)
In order to evaluate the Physical properties Of the Hybrid leaf of 4 of fayer tobacco for pu re in the phase of the drying under tropical conditions and to Evaluate the yield of dry matter and to detennine the cost benefit of the treatments in study, it was carried out the present work in the cured of house of Tobaccos of the Peru S. A. in Juan Guena district, County and department of San Martín, altitude 232 m. s. n. m., Longitude West 76º 30 (15", South Latitude 06º 30 (15", Tº mediatas Annual 26.3ºC and precipitation 1047 mm. lt was driven Completely under the Design ·Block. Randomized with 4 treatments and 4 repetitions. The treatment 1 that corresponds to the hybrid tobacco ª59107 x 59105", it was the one that presentad a better characteristic to be used for the layer of pure, when showing in the leaves 9.11 elasticity, 8.44 flat, 75% combustibility, 18.22% humidity, 9.8 of ashy and golden brown color. The treatments 1, 3· and 4, coming from Sumatra the hybrid ones that showed to have a golden brown coloration were (93.63, 89.83 and 91.46%) and the hybrid coming from Cigar Nicaragua shows a reddish gilded coloration (88. 76%) in more percentage. The humidity in the house of the curad one fluduated at 7. 00 in the moming among 90 to 100%, 12 of the meridian among 40 to 80% and the 6.00 p. m. among 45 to 80%. The ·hybrid ones that presentad better combustibility in the leaf were those coming from Sumatra and their averages fluctuate from 75.00 to 89.29%. Showing that they have bigger accumulation of potassium in their cells. The treatments 1, 3 and 4 that it corresponds to the hybrid tobaccos Sumatra presentad bigger width (25.06, 24.54 and 24.58 cm) and longitude (41.63, 41.26 and 41.93 cm) of the leaf. The treatments 3, 4 showed bigger percentage of green leaf without stains (59.22 and 62.87%) tuming out to be the most resistant to the attack of illnesses of Cercospora nicotlanae and it would Altemate altemata. The treatments 1,3, 4 obtained bigger yields in dry leaf (1744.30 - 1827.14 Kg/ha) with net value of produdion that variad of 8.37 and 12.48%.